BOOK REVIEW Qualitative Data Analysis: A User Friendly Guide for Social Scientists - Bilmanoch, Sasiphan (Siam Communication Review, 2019)
It’s a sign of the times that this resource came to my attention via the Internet, although it is available as a printed book as well. As I now supervise and advise a number of graduate students on a continuing basis, I was looking for student-friendly resources that I could recommend to new MA students, to assist them developing research proposals. After choosing an interesting topic, the initial enthusiasm of these trainee researchers is often really tested by the need to plan their project in detail and justify how to analyse the data collected. Most of these Arts or Social Science students have little or no background in data analysis or knowledge of statistics. So accessible guides like this are extremely useful introductions for the student to develop, at their own speed, their own ideas for analysing the particular data they intend to collect. These suggestions or proposals can then be discussed with supervisors or advisors, for approval or improvement.